Hubungan Sikap dan Gaya Hidup Konsumsi Junk Food dengan Kejadian Overweight di SMA Kristen Immanuel Medan: Penelitian - Tesalonika R.M. Panggabean; Alam Bakti; Ernawati Nasution; Dhani Syahputra Bukit (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Attitudes and lifestyle related to food consumption play a key role in determining adolescents’ nutritional status, particularly concerning overweight. The rising trend of junk food consumption among teenagers in recent years has raised concerns about its physical and psychological health impacts. This study aimed to examine the relationship between attitudes and lifestyle related to junk food consumption and the incidence of overweight among students at Immanuel Christian Senior High School in Medan. Using a descriptive-analytic design with a cross-sectional approach, the study involved 56 students selected through total sampling. Data were collected via questionnaires (assessing attitudes, dietary patterns, physical activity, and snacking habits) and BMI measurements. Chi-square analysis revealed that most students had a moderate attitude toward junk food (69.6%), and a moderate lifestyle category was also dominant (87.5%). A significant association was found between attitudes toward junk food and overweight (p = 0.008), while no significant relationship was found between lifestyle and overweight (p = 0.108). These findings indicate that permissive attitudes toward junk food are significantly associated with increased risk of overweight. The results are expected to serve as a basis for schools and parents to strengthen health education and promote healthy eating habits among adolescents.